2020
DOI: 10.1039/d0ra04966b
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon and palm oil fuel ash as microwave absorbers for microwave-assisted pyrolysis of oil palm shell waste

Abstract: In this study, the effects of two microwave absorbers (MWAb) or catalysts, namely activated carbon (AC) and palm oil fuel ash (POFA), were investigated in microwave pyrolysis of oil palm shell (OPS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In contrast, phenol was the dominant component in the bio-oil phase at 44.2% and 40.9% for 400 °C and 700 °C runs, respectively. Increasing the pyrolysis temperature reduces amounts of phenol and phenolic compounds (Idris et al 2021), but increases the other chemical components because large chemical molecules tend to be broken down into many smaller molecules, as also found in the previous study by Chuayjumnong et al (2020). After MW pyrolysis the solid phase of the mixture sample, which remained in the quartz reactor, was separated to AC and residual OPS by particle size.…”
Section: Product Quality Of Crude Bio-oil (Aqueous Phase and Bio-oil ...supporting
confidence: 57%
See 1 more Smart Citation
“…In contrast, phenol was the dominant component in the bio-oil phase at 44.2% and 40.9% for 400 °C and 700 °C runs, respectively. Increasing the pyrolysis temperature reduces amounts of phenol and phenolic compounds (Idris et al 2021), but increases the other chemical components because large chemical molecules tend to be broken down into many smaller molecules, as also found in the previous study by Chuayjumnong et al (2020). After MW pyrolysis the solid phase of the mixture sample, which remained in the quartz reactor, was separated to AC and residual OPS by particle size.…”
Section: Product Quality Of Crude Bio-oil (Aqueous Phase and Bio-oil ...supporting
confidence: 57%
“…Pianroj et al (2016) demonstrated high-intensity MAP with two magnetrons. Chuayjumnong et al (2020) modified a household MW oven to study MAP with OPS and AC. They found that a large specific surface area of the AC can increase both yield and quantity of bio-oil.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, there was growing research interest on the utilization of alternative origin of waste materials from industry and agriculture for activated carbon production [24][25][26][27]. A sizable numbers of reports have been published on generation of activated carbon from agro waste such as palm shell [28,29], coconut shell [30,31], corn cob [32], olive stones [33] and walnut shell [34], coir pith [35], rice bran [36], chickpea husks [37], oil palm shell [38], etc. Ioannidou et al [23] have used the agricultural residues such as soya stalks, corn cobs, rapeseed stalks, and olive kernels as precursors for the generation of activated carbon.…”
Section: Activated Carbonmentioning
confidence: 99%
“…The mechanism of electromagnetic wave radiation protective materials includes: first, the wave reflection mechanism uses metal, this is because metals have electrons that are always moving [15]. Second, the absorption mechanism, where the material must have an electric or magnetic dipole, such as ZnO, SiO 2 , TiO 2 , BaTiO 3 for electric dipole materials or Fe 2 O 3 , Fe 3 O 4 for magnetic dipole materials [16].…”
Section: The Aim and Objectives Of The Studymentioning
confidence: 99%